The resilience strategies of tourism SMEs in Bengkulu's coastal ecotourism zone: Resilience Strategies of Tourism SMEs - Rahmat Putra Ahmad Hasibuan; Maulida Khairani; Nur Fadhilah Ahmad Hasibuan (Institute of Computer Science (IOCS), 2026)
Tourism SMEs in Bengkulu's coastal ecotourism areas frequently face environmental and economic disruptions that challenge their business sustainability. This study explores how these SMEs build and maintain organizational resilience amidst uncertainty. Using a qualitative approach, data were collected through in-depth interviews with selected SMEs from the culinary, souvenir, homestay, local fashion, and transportation sectors. Thematic analysis revealed that resilience among tourism SMEs is shaped through three interrelated dimensions: cognitive, behavioral, and contextual resilience. Cognitive resilience emerges from local awareness, anticipation, and collective understanding that enable SMEs to recognize and respond to environmental changes. Behavioral resilience is demonstrated in adaptive practices, flexibility, and innovation that transform limited resources into creative responses. Contextual resilience is rooted in social networks, partnerships, and informal cooperation that strengthen collective adaptive capacity despite limited institutional support. These findings highlight that resilience in coastal tourism SMEs is not a static trait but a cyclical process of learning, adaptation, and collaboration. This study contributes to the understanding of resilience in the tourism context of developing countries and offers insights for strengthening the sustainability of coastal based SMEs through locally embedded adaptive strategies.